PROPERTIES OF EDIBLE FILM FROM MODIFIED SAGO STARCH PRECIPITATED BY BUTANOL - Riska Surya Ningrum; Dewi Sondari; Putri Amanda; Bernadeta Ayu Widyaningrum; Dian Burhani; Fazhar Akbar; Yulianti Sampora (Jurnal Sains Materi Indonesia, 2020)
ROPERTIES OF EDIBLE FILM FROM MODIFIED SAGO STARCH PRECIPITATED BY BUTANOL. The edible film is a thin layer that can be used as food packaging and safe for consumption. Starch is a material that can be used as an edible film because it is biodegradable, non-toxic, able to form a strong and transparent film. In this research, sago starch has been precipitated using butanol for 1, 2, 3, 4, and 5 hours. Precipitated sago is reacted with 3% glycerol and then formed into a film by printing it on a petri dish. Characterizations of edible films are FTIR, contact angle, water solubility, swelling power, WVTR, and mechanical properties (thickness, tensile strength, and elongation). Edible film (B2) has the best mechanical properties, that is high hydrophobicity (contact angle is 60,351 degree), tensile strength (6,8843 N/mm2), and elongation (49,5081 %), also low water solubility (0,3352 %), moisture content (18,6005 %), and WVTR (0,02986 g s-1 m-2).